NGC 6860, Mrk 915, and MCG -01-24-012: I. Spatial anticorrelation between cold molecular and ionized gas distributions in Seyfert galaxies - Dall'Agnol de Oliveira, Bruno; Storchi-Bergmann, Thaisa; Nagar, Neil; Garcia-Burillo, Santiago; Riffel, Rogemar A.; Wylezalek, Dominika; Kukreti, Pranav; Ramakrishnan, Venkatessh (Astronomy and astrophysics, 2025)
We present a study of the cold molecular versus ionized gas distribution in three nearby Seyfert galaxies: NGC 6860, Mrk 915, and MCG -01-24-012. To constrain the cold molecular flux distribution at ∼0.5−0.8″ (∼150−400 pc) scales, we used data from the CO(2−1) emission line, obtained with the Atacama Large Millimeter/submillimeter Array (ALMA). For the ionized gas, we used Hubble Space Telescope (HST) narrowband images, centered on the [O III]λλ4959,5007 emission lines. Within the inner kiloparsec of the three galaxies, we observe gaps in the CO emission in regions co-spatial with the [O III] flux distribution, similarly to what has recently been observed in other active galaxies. Of our original sample of 13 nearby active galactic nucleus (AGN) sources, 12 objects present the same trend. This indicates that CO molecules might be partially dissociated by AGN radiation or that there is a deficit of cold molecular gas on nuclear scales driven by ionized gas outflows and/or jets. If so, this represents a form of AGN feedback that is not captured when only outflow kinematic properties, such as mass outflow rates, are considered. We also discuss how part of the molecular gas might still be present in hotter H2 phases, as has already been observed in other objects.